Sheltering women: Jung Park, Y, Fedler, J & Danger, Z (eds) (2000) Reclaiming women's spaces: New perspectives on violence against women and sheltering in South Africa. Johannesburg: NISAA Institute for Women's Development. ISBN 0-620-25733-4. - Lempert, Lora; Shefer, Tammy (PINS-Psychology in Society, 2026)
Reclaiming women's spaces (2000) provides recent theoretical and applied work about the range and depth of violence against women in South Africa. Serving as an invaluable resource text for a wide audience - including legislators, scholars, lecturers, NGOs, international and local researchers, theorists and practitioners - the book provides a comprehensive current and historical account of legal, political, organisational and practice-based developments in the field of violence against women.